Striving for a holistic view: student teachers’ views on teacher competencies - Heikkilä, Mirva; Mankki, Ville; Varis, Sotiria; Iiskala, Tuike; Metsäpelto, Riitta-Leena; Mikkilä-Erdmann, Mirjamaija (Taylor & Francis, 2026)
This article examines how Finnish student teachers describe teacher competencies. Investigating teacher competencies as a comprehensive whole and using an established framework have been rare in teacher education research, despite being crucial for fluent transitions from teacher education to working life. The participants (N = 73) were studying in the primary and special teacher education programmes of a Finnish university, and had just completed their first teaching practicum (Spring 2023). Textual data were collected through written reflections on the topic, which students completed as part of their coursework. This data were analysed using a theory-driven qualitative content analysis informed by the multidimensional adapted process model of teaching (MAP). The findings indicated that student teachers describe teaching as a multifaceted profession, emphasising pedagogical knowledge, relational skills, and emotional competency. Reflections on content knowledge were strikingly few. Competencies that were scarcely mentioned included practical knowledge, contextual knowledge, digital skills, and diversity and intercultural competencies. This study contributes valuable insights on the intersection of teacher education and working life to be used in teaching, curriculum development, and programme design. Additionally, the study discusses the use of competency models in empirical research.